2017
DOI: 10.18203/2349-2902.isj20175912
|View full text |Cite
|
Sign up to set email alerts
|

Liver biopsy in gall stone disease: a prospective study in patients undergoing cholecystectomy

Abstract: Background: Cholelithiasis has affected mankind since many centuries. It not only affects the biliary tree but also has adverse effects on the hepatic parenchyma, which can get further complicated due to infected bile. Early intervention in these cases not only retards the unwanted effects but also prevents irreversible damage to liver. Aim of study was to see the effect of gallstone disease on liver in patients of GSD (Cholelithiasis, Chronic cholecystitis, CBD Stones).Methods: All patients being subjected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…Liver histology changes were present in six patients (75%), and all six patients had portal tract infiltration and cholestasis, and bile culture was positive in five patients. This observation aligns with the study findings of Patel G. et al [ 3 ]. Consequently, the present study suggests a positive correlation between symptom duration and liver histological changes, indicating that longer durations of symptoms increase the likelihood of significant changes in liver biopsy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Liver histology changes were present in six patients (75%), and all six patients had portal tract infiltration and cholestasis, and bile culture was positive in five patients. This observation aligns with the study findings of Patel G. et al [ 3 ]. Consequently, the present study suggests a positive correlation between symptom duration and liver histological changes, indicating that longer durations of symptoms increase the likelihood of significant changes in liver biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in this study, the mean age of the patients was 39.28 ± 13.73 years, and most patients were female. These findings are similar to the previous reports [ 3 , 4 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, Patel et al also observed histopathological cholestasis in 10% of their patients who underwent uncomplicated cholecystolithiasis cholecystectomy. 9 , 10 The possibility of occurrences of resolved subclinical cholestatic events or undetected biliary diseases of undetermined clinical importance was raised in these previous studies, and this is reinforced by the findings of the current study.…”
Section: Discussionsupporting
confidence: 64%